(NnOWYE KARTY DLQ WYS[EJ [KOLY (B:s (NSISTEMNOE GEOGRAFI^ESKOE KARTOGRAFIROWANIE sssr I MIRA (B: [(NsBORNIK STATEJ(B] /s - (NsALI]EW(B, (NkONSTANTIN aLEKSEEWI^s; (NmOSKOWSKIJ GOSUDARSTWENNYJ UNIWERSITET IM(B. (Nm(B.(Nw(B. (NlOMONOSOWAs (NgEOLOGI^ESKIJ FAKULXTETs ((NmOSKWA (B:s (Nmgu(B,s, 1987)
(NbIBLIOGR(B. (NW KONCE ST(B.s
Keywords: (NgEOGRAFI^ESKIE KARTY I ATLASYs -- (NiZU^ENIE W WYS[EJ [KOLE (B- (NsBORNIKIs; (NkARTOGRAFIQs -- (NsBORNIKIs